Pengaruh Kualitas Pelayanan Perawat terhadap Kepuasan Pasien Rawat Inap di RSUD Dr. R. M Djoelham Kota Binjai - Lidia Apriani; Irwan Nasution; Agung Suharyanto (Universitas Medan Area, 2022)
This paper aims to determine the effect of nurse service quality on inpatient satisfaction at the Regional General Hospital Dr.R.M. Djoelham City of Binjai. Researchers using the theory of Tjiptono (2012) suggests that there are five dimensions of service quality (Physical Evidence, Reliability, Responsiveness, Assurance and Empathy). This type of quantitative research uses design. A sample of 100 patients was taken using proportional random sampling technique. The analysis used validity and reliability tests with Cronbach's Alpha. Classical assumption test includes normality test, multicollinearity test and heteroscedasticity test. To test the hypothesis using multiple linear regression. All tests used the SPSS computer program. From the results of the research conducted, physical evidence (3.052), reliability (2.271), responsiveness (3.694), assurance (3.049) and empathy (2.365) together have a positive and significant effect on inpatient satisfaction. And R2 of (0.699) indicates that it is 69.9%.